The aging male project (Medical Journal of Indonesia, 2001)
With an increasing life expectancy and a decreasing reproduction rate, the population structure changes. A Jenapharm R & D program investigates the endocrinology of aging men. In men, a decrease in production of sex steroids and other hormones with age can be observed. The typical patterns of daily rhythmicity become less distinct. This is part of a very complex picture in which not only isolated hormones are involved, but also the influence of hormones on each other. Many factors from the external and intemal environment mediated by neurotransmitters constantly affect the highly sensitive hormonal balance. Therefore, aging has also been defined as "the gradual dysfunction of homeostatic processes". Declining testosterone (T) levels are involved in 'andropausal' symptoms in men: loss of libido, erectile dysfunction, insulin receptor resistance, obesity, osteoporosis, disturbances of lipid metabolism, myocardial and circulatory disturbances, impaired well-being and mood. Data are derived from studies in hypogonadal men treated by T replacement. In such parients under T treatment libido increases, fat mass decreases, muscle strenth, bone mineral density and erythropoesis increase. Whether the symptoms of andropause in aging men could successfully be treated by T substitution remains to be investigated. Negative effects of T, especially on the prostate and the cardiovascular system, are under discussion. There is increasing evidence that low T levels seem to be a risk factor for both the prostate and the cardiovascular system. Jenapharm's new testosterone undecanoate formulation for intramuscular injection can be administered every three months. T levels remain within the physiologic range. No supraphysiologic peaks occur. In women, estrogens have beneficial non-genital effects. Studies concentrate on synthetic estrogens for men without feminizing properties such as gynecomastia and reduced testicular size. Several derivatives of 17- alpha estradiol have been synthesized some of which show selectivity for the central nervous system. CNS effects have been demonstrated in female and male animals. Cardiovascular protection by estrogens has been shown in animal and human studies. Atherosclerotic plaque size was reduced after estrogen injections in cholesterol-fed rabbits. Phytoestrogen-fed monkeys had lower total cholesterol and LDL cholesterol and higher HDL cholesterol. Apart from atherosclerotic lesions, coronary artery vascular reactivity was improved. Some of these experimental findings were confirmed in human studies in postmenopausal women with and without estrogen treatment. Whether all of the described estrogenic effects can be seen in men remains to be investigated. (Med J Indones 2001; 10: 127-33)Keywords : aging, andropause, testosterone, estrogens